PENGARUH PENGANGGURAN, INFLASI DAN INVESTASI TERHADAP PARTISIPASI ANGKATAN KERJA DI PROVINSI JAWA TENGAH PERIODE 1994 – 2023 - Subchanifa, Dian Pujiatma Vera; Riyadi, Muhammad Wahyu (Politeknik Negeri Lhokseumawe, 2025)
Abstract : This research aims to analyze the influence of unemployment, inflation and investment on the labor force participation rate in Central Java Province during the period 1994-2023. By using time series data and multiple linear regression methods, the research results show that unemployment and investment have a significant influence on labor force participation. Unemployment has a positive effect, meaning that an increase in unemployment is accompanied by an increase in labor force participation. On the other hand, inflation does not have a significant effect on labor force participation. The coefficient of determination (R²) value of 77.43% indicates that the independent variables in this study are able to explain variability in labor force participation, while the rest is influenced by other factors. The results of this research can be a reference for policy makers to increase labor force participation through reducing unemployment and increasing investment.Keywords : Unemployment, Inflation, Investment, Labor Force Participation, Economic Policy